2019
DOI: 10.18070/erciyesiibd.338123
|View full text |Cite
|
Sign up to set email alerts
|

Çalışanların otantik ve hizmetkâr liderlik algılamalarının, performansları üzerindeki etkileri: Kayseri Organize Sanayi Bölgesinde bir işletme uygulaması

Abstract: Liderlik geçmişten bugüne bireylerin, örgütlerin ve toplumların ilgisini çeken önemli bir konudur. Değişen ve gelişen koşullara göre şekil alan liderlik türleri arasında yer alan ve son zamanlarda daha çok incelenen otantik ve hizmetkâr liderlik konuları bu çalışmanın odağını oluşturmaktadır. İşletmenin devamlılığı için lider kadar önemli bir diğer unsur da işletmenin çalışanları ve onların performanslarıdır. Algılanan liderlik tarzı ile çalışanların ortaya koyacakları performans arasındaki ilişkilerden hareke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…The SET (Blau, 1964) also indicates that servant nurse leaders enhance nurses' JP by serving as role models for better performance while providing individual, organizational and community health services (Liden et al, 2008(Liden et al, , 2014. This result supports the results of the studies of the relationship between SL and JP in the sectors other than nursing (Zehir et al, 2013;Chiniara andBentein, 2016, Karacao glu andSatır, 2019;Saleem et al, 2020). A study conducted with nurses ( € Ozer, 2019) did find a significant correlation between SL and JP, while another study found no significant effect (Sanchez, 2019).…”
Section: Effect Of Nurse Managers' Servant Leadershipsupporting
confidence: 69%
See 2 more Smart Citations
“…The SET (Blau, 1964) also indicates that servant nurse leaders enhance nurses' JP by serving as role models for better performance while providing individual, organizational and community health services (Liden et al, 2008(Liden et al, , 2014. This result supports the results of the studies of the relationship between SL and JP in the sectors other than nursing (Zehir et al, 2013;Chiniara andBentein, 2016, Karacao glu andSatır, 2019;Saleem et al, 2020). A study conducted with nurses ( € Ozer, 2019) did find a significant correlation between SL and JP, while another study found no significant effect (Sanchez, 2019).…”
Section: Effect Of Nurse Managers' Servant Leadershipsupporting
confidence: 69%
“…Employees who consider that their managers have positive SL behaviors take their managers as role models for their business-oriented behaviors and moral aspects and feel safe in their working environment; thus, they are motivated by their managers' SL style to develop themselves and show higher performance (Hu and Liden, 2011). Previous studies have found a significant relationship between managers' SL and employees' unit performance (Liden et al, 2014), JP (Zehir et al, 2013;Chiniara and Bentein, 2016;Karacao glu and Satır, 2019;Saleem et al, 2020) and individual performance (Lee et al, 2020). On the other hand, studies conducted with nurses have reported different findings: Sanchez (2019) found that SL significantly affected employees' job thriving but had no significant effect on their JPs, while € Ozer (2019) found a statistically significant relationship between nurse managers' SL behaviors and nurses' performance.…”
Section: Nurses' Innovative Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Görev performansının, teknik işlere katkı sağlaması ve işin resmi bir parçasını oluşturması gibi iki temel özelliği bulunmaktadır (Rotundo & Sackett, 2002). Hammaddenin ürün haline gelmesi, envanter tutmak, satın almanın yapılması, ürünlerin dağıtımı, astlar arasında koordinasyon sağlanması, muhasebe kayıtlarının tutulması gibi kurumda temel dönüşümün sağlayan faaliyetler görev performansı ile ilgilidir (Karacaoğlu & Satır, 2019).…”
Section: İş Performansıunclassified
“…İş performansı, genel olarak bireysel olarak gösterilen çabaların, örgütün değerini arttırması sağlayan çabalar toplamıdır (Lopez-Cabarcos, 2022). Hizmetkar liderlik ve iş performansı üzerine yapılmış çeşitli araştırmalarda, hizmetkar liderliğin, iş performansı, bireysel performans, görevsel-bağlamsal performans gibi performans türleri üzerinde olumlu etkilerinin olduğu tespit edilmiştir (Chiniara & Bentein, 2015;Karacaoğlu & Satır, 2019;Liden vd., 2008;Ürü Sanı vd., 2013).…”
Section: Introductionunclassified